Productivity analysis focusing on internal combustion engine vibration when using local fuels and additives - Reyes Campaña , Guillermo Gorky; Sánchez Delgado, Juan Andres; Rojas Bravo, Steven Sebastián (Journal of business and entrepreneurial studie, 2023)
The purpose of this article is to analyze the vibrations and behavior of an internal combustion engine of three vehicles: A1, J1, K1 which are exposed to both the geography, relief and road conditions of the Metropolitan District of Quito. To implement the quantitative methodology in the research it is important to perform a complete analysis of the vehicle based on its technical data sheet: A1, J1, K1, in order to identify both fuel consumption and the use of additives to reduce the friction that cause vibrations in the engine, especially the condition of the road. In addition, it is important to check how the level of vibrations can be reduced, the percentage of fuel when using additives and to verify the data provided by the vibration study of each vehicle. The results show that the tests carried out at 3500 RPM in vehicle A1 show a value of 27%, in vehicle J1 a value of 17% and vehicle K1 a value of 15%, these values are related to the use of additives. The results of the research are linked to field tests, individual tests, comparison of results and discussion of the feasibility of each of the tests performed on each vehicle to find similarities or marked differences.